PEMANFAATAN MEDIA IT PADA MATA PELAJARAN IPA BERDASARKAN GAYA BELAJAR KELAS V SDN GAJAHMUNGKUR 04 - Sikky Rokhayah (COLLASE (Creative of Learning Students Elementary Education), 2023)
This study aims to analyze the use of IT media in science lessons in terms of visual, auditory, and kinesthetic learning styles, as well as analyze the factors that influence student learning styles. Researchers use a type of descriptive narrative qualitative research. The source of the data in this study were fifth grade students at SD N Gajahmungkur 04. Data collection techniques included interviews, observation and documentation. While the data analysis techniques in this study are data reduction, data display, and conclusion drawing/verification. The results of this study are; (a) Students with a visual learning style with image orientation. Students will easily remember material through visual associations. IT media used in the form of PowerPoint and pictures and videos; (b) Students with an auditory learning style are students who are reactive to sound. IT media that can be used are tape recorders and videos; (c) Students with a kinesthetic learning style read material with a pattern of moving their lips. The kinesthetic characters that exist in students with kinesthetic learning styles include liking to learn through manipulation and practice. IT media that can be used is in the form of learning game applications; (d) Factors that influence student learning styles are internal factors and external factors. Keywords: learning styles, media, IT